Innovative component of the spread of organic farming in the context of the implementation of the concept of sustainable development on the example of the Southern region of Ukraine - Kuznietsova, M.; Labunska , O. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2025)
Goal. To analyze the role of the innovation component in the development of organic farming as one of the areas that contributes to the achievement of global sustainable development goals on the example of the Southern region of Ukraine.Methods. General scientific methods were used — analysis and synthesis, comparison, scientific abstraction, generalization, graphic research methods. To reveal the topic of the article, the authors developed survey forms and conducted a survey of higher education institutions and scientific institutions of the agro-industrial sector of the Southern region of Ukraine regarding the features, effectiveness and financing of their research activities in the agricultural sector.Results. Sustainable development goals and the role of organic production in their realization, the current state of organic production in European countries in terms of the growth of organic land over the past 10 years and the number of organic operators were analyzed. The author has collected relevant data on the development of organic production in the regions of Ukraine. It is proved that this area of agricultural activity is knowledge-intensive, and its spread is based on strengthening the innovation component. The data for 2023 for the Southern region of Ukraine are analyzed according to the following indicators: the number of researches conducted for the agro-industrial complex; results of research implementation in the agro-industrial complex; uniqueness of research results; availability of elements of innovation and research infrastructure; sources of funding for research carried out by higher education institutions (HEIs) and scientific institutions of the agricultural sector. The author proves the need to strengthen state support for the agro-industrial sector in order to stimulate the development of organic production by increasing budgetary funding for research in this area.Conclusions. Based on the survey conducted in higher education institutions and scientific institutions of sectoral subordination in the Southern region of Ukraine, the authors concluded that the availability of a certain number of scientific developments and innovative proposals with a high scientific level and their implementation in the agro-industrial sector will be the key to the accelerated development of organic production as a priority method of agriculture in our country.